Akibat Hukum Pengaturan Bukti Pendaftaran Dalam Pengesahan Pendirian Perseroan Terbatas Berdasarkan Undang-Undang Cipta Kerja - Swari, I Gusti Agung Ayu Astri Nadia; Yusa, I Gede (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022), 2022)
The purpose of this study is to determine and analyze the legalization of the establishment of a limited liability company and the legal consequences of the decree of the Minister of Law and Human Rights concerning the legalization of the legal entity of the establishment of a limited liability company against the Job Creation Act. This legal research is a normative legal research in which an assessment of the applicable laws and regulations is carried out and uses secondary data as the main data. Based on the results of the research, the following conclusions can be formulated: (1) The regulation on the legalization of a Limited Liabilty Company legal entity based on the Job Creation Act Article 109 Paragraph (2) which stipulates that the Company obtains the status of a legal entity after being registered with the Minister and obtaining proof of registration is valid; and (2) The process of ratification of Limited Liabilty Company is not effectively implemented in the mechanism of legalization of a legal entity of Capital Alliance Limited Liabilty Company which can cause the establishment of a legal entity of Limited Liabilty Company to become null and void.